HUBUNGAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR MATA PELAJARAN PENGERITINGAN RAMBUT SISWA JURUSAN TATA KECANTIKAN SMK N 7 PADANG - Noviarti, Geni Eka; Hayatunnufus, Hayatunnufus; Yanita, Merita (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2015)
This research is motivated by the curling value of students SMK N 7 Padang thatoccured in the low category and did not reach KKM, the low value caused by theunenthusiastic students and less active in the learning process, low learning spirit,less ready to learn, less creative and the tasks are not completed properly. Thisresearch generally aims to reveal the relationship between learning motivation andlearning results of curling Subject in Beauty department of SMK N 7 Padang. Inparticularly this study aims to describe 1) students learning motivation in curlingsubject of Beauty Department SMK N 7 Padang, 2) the results learning ofstudents curling Subject beauty department SMK N 7 Padang, 3) the relationshipbetween motivation and learning results of students curling subject BeautyDepartment SMK N 7 Padang. The type of this research is quantitativedescriptive by using correlational approach. The research population is the studentof SMK N 7 Padang class XI and XII registered on semester January to June2013/2014 Beauty Department SMK N 7 Padang who have followed curlingsubjects were 36 students, consist of 2 classes. The sampling technique used inthis research is total sampling. Based on the results of the data analysis, researchresults show that learning motivation variables included in the low category with apercentage of 36.11%, and the variable results study of curling subjects includedin very less with a percentage of 47.22%. The relationship between learningmotivation variable (X) with variable results study of curling subject (Y) has asignificant and positive relationship with a correlation of 0.706, the results ofcorrelation coefficient significance test t_hitung> T_ (table) (5,805> 2,032).Therefore, both teachers and parents need to further increase student motivationslowly so that the students feel confident and eager to learn more diligently andget satisfactory of learning results.Keywords : Motivation With Learning Outcomes